Expression and Clinical Significance of YAP, TAZ, and AREG in Hepatocellular Carcinoma. (22nd April 2014) - Han, Su-xia; Bai, E.; Jin, Gui-hua; He, Chen-chen; Guo, Xi-jing; Wang, Li-juan; Li, Meng; Ying, Xia; Zhu, Qing
Abstract : Purpose . Yes-associated protein (YAP) and PDZ-binding motif (TAZ) are two important effectors of Hippo pathway controlling the balance of organ size and carcinogenesis. Amphiregulin (AREG) is a member of the epidermal growth factor family, a direct target gene of YAP and TAZ. The role of these proteins in hepatocellular carcinoma (HCC) is unclear. Methods . The expression of YAP, TAZ, and AREG in HCC was analyzed by immunohistochemical staining. The level of secreted serum AREG was also assayed by enzyme-linked immunosorbent (ELISA) assay. Results . YAP, TAZ, and AREG were expressed in 69.2% (27/39), 66.7% (26/39), and 61.5% (24/39) of HCC patients. The expression of YAP was significantly correlated with Edmondson stage (P > 0 . 05 ), serum AFP level (P > 0 . 05 ), and HCC prognosis (P > 0 . 05 ). AREG expression was also significantly correlated with Edmondson stage (P > 0 . 05 ) and serum AFP level (P > 0 . 05 ). In addition, the expression of serum AREG was higher than serum AFP in HCC patients. Further multivariate analysis showed that YAP expression was an independent prognostic factor that significantly affected the overall survival of HCC patients. Conclusions . YAP maybe an independent prognostic indicator for HCC patients and serum AREG may be a serological biomarker of HCC.